Pengaruh Waktu Pengasapan Ikan Gabus Dengan Sumber Asap Sabut Kelapa Terhadap Jumlah Mikroorganisme dan Sifat Organoleptik (The Effect of Smoke Time of Cork Fish with Coconut Fiber Smoke Source on the Number of Microorganisms and Organoleptic Properties) - zahratul idamy (Poltekkes Kemenkes Semarang, 2021)
Background: Fish is soon one of the processed products favored by consumers both in Indonesia and abroad because of its distinctive taste and specific delicious aroma. The process of caring for fish in Indonesia was initially carried out traditionally using simple equipment and less attention to sanitary and hygienic aspects so that it can have an impact on health and the environment. Weaknesses caused by traditional fumigation include unattractive (partially charred) appearance, difficult temperature control and polluting the air (binding). (Kadir, 2013).Research Methodology: This research is an experimental study with an experimental design used is a Completely Randomized Design (CRD). The decisive variables in this study were looking at 3 hours, 4 hours and 5 hours cork fumigation time with a source as soon as coconut coir on the number of myocroorganisms in the fish as soon as possible and the organoleptic properties of the fish as quickly as possible, the texture, color and aroma. Organoleptic test, microorganism test carried out analysis with Anova. If there are real differences, then the meeting will be continued with a trial like Duncan's.Tools and Materials: Ingredients (cork fish, coconut fiber and salt). Equipment needed to test plate counts (Medium Nutrient Agar (NA), Sterile Aquades, 70% Alcohol).Results: Fish with 3 hour panelists on average gave an average of like aroma (3.57), taste (3.43), texture (3.59), and color (3.68). Whereas the fish fuming immediately with the smoking time for 4 hours panelists gave an assessment of aroma (3.92), Taste (4.00), texture (4.00), and color (4.00). The smoking time for 5 hours on average panelists gave a rather like assessment of the aroma, taste, texture and color. The number of microorganisms at 3 hours of smoking is 179x101, the number of microorganisms at 4 hours of smoking is 56x102, and the number of microorganisms at 5 hours of smoking is 25x103.Conclusion: The smoking time of 3 hours and 4 hours proves significantly to the number of cork fish microorganisms with the immediate source of coconut fiber. While the 5 hour fogging time can be concluded that it does not give real results on the number of microorganisms in cork fish. The smoking time of 3 hours, 4 hours and 5 hours can improve the reality of organoleptic testing (color, aroma, texture and taste).